2009
DOI: 10.1242/jcs.043042
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of vimentin to the cell surface by β3 integrin and plectin mediates adhesion strength

Abstract: Much effort has been expended on analyzing how microfilament and microtubule cytoskeletons dictate the interaction of cells with matrix at adhesive sites called focal adhesions (FAs). However, vimentin intermediate filaments (IFs) also associate with the cell surface at FAs in endothelial cells. Here, we show that IF recruitment to FAs in endothelial cells requires β3 integrin, plectin and the microtubule cytoskeleton, and is dependent on microtubule motors. In CHO cells, which lack β3 integrin but contain vim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(148 citation statements)
references
References 47 publications
7
136
0
Order By: Relevance
“…Inflammation is considered to be a major consequence of SASP, which proposes that senescent fibroblasts are primed to become proinflammatory cells. Despite lacking a secretory signal sequence, vimentin is externalized on the cell surface and secreted in various physiological conditions that involve induction of proinflammatory signals, suggesting a possible phenotypic connection to SASP (42,43,50,51). We therefore sought to measure secreted vimentin using our polyreactive 9H4 antibody as a potential readout of senescent cells in vitro and in vivo.…”
Section: H4 Recognizes Vimentin and Oxidative Posttranslational Modimentioning
confidence: 99%
“…Inflammation is considered to be a major consequence of SASP, which proposes that senescent fibroblasts are primed to become proinflammatory cells. Despite lacking a secretory signal sequence, vimentin is externalized on the cell surface and secreted in various physiological conditions that involve induction of proinflammatory signals, suggesting a possible phenotypic connection to SASP (42,43,50,51). We therefore sought to measure secreted vimentin using our polyreactive 9H4 antibody as a potential readout of senescent cells in vitro and in vivo.…”
Section: H4 Recognizes Vimentin and Oxidative Posttranslational Modimentioning
confidence: 99%
“…Several studies have suggested that the intermediate filament protein vimentin is associated with focal adhesions and with the regulation of focal adhesion size and stabilisation of ECM-cell adhesion sites (Bhattacharya et al, 2009;Tsuruta and Jones, 2003). Because vimentin and nestin are binding partners, we wanted to study whether nestin was also associated with focal adhesions and what the implications of this are.…”
Section: Nestin Regulates the Localisation Of Pfakmentioning
confidence: 99%
“…Moreover, through integrin-linked kinase, integrin can regulate expression and function of vimentin. The levels of vimentin and integrin play a key role in tissue homeostasis as well, and their hyperexpression leads to tumorigenesis [25,26] . We detected and observed that the mRNA expression levels of α v -integrin and vimentin could be mediated by heparin treatment.…”
Section: Effect Of Heparin On Brdu Incorporation and Ki67 Expression mentioning
confidence: 99%